Improving the process and equipment for tablets pressing - Spolovych, Maksym; Prokop, Andrii; Chepeliuk, Olena (My University, 2020)
Because of differences in the raw materials density and incomplete filling of the tablet presses dies, there are deviations in the mass of the finished solid dosage forms. The task of a dosing accuracy increasing requires a solution. The rational idea of improving the tablet press dosing mechanism is to adjust the size of the connecting hole between the feed cup and the feeder. It is proposed to change the relative position of the windows of the feeder and the feed cup, which are connected, by rotating the damper located in the ring between the cup and the feeder housing. This mechanism is much easier, faster and more accurately allows you to adjust the flow rate of the tableting mass. The proposed design is simpler and more reliable, as it does not require additional operations to configure. The inclined plane remains in a static position, so the error in braking the flow is smaller than when turning it. Improving the design of the feeder of the rotary tablet press by replacing the lever mechanism on the rotary damper, the position of which regulates the amount of material entering the mixers, simplifies the feed cup design, increases the efficiency of die filling and, accordingly, the dosing accuracy, facilitates the feeding device maintenance and increases its reliability in operation.
Keywords: кафедра машин і апаратів харчових та фармацевтичних виробництв; accuracy; damper; dosage; feeding device; rotary tablet press; tableting mass; точність; заслінка; дозування; пристрій для подачі; ротаційний прес для таблеток; таблетувальна маса